Dynamics of exposure to mercury in a population of the upper Madeira River, Rondônia – Brazil - Serra , Clarisse Vasconcellos; Silva, Tania Machado; Bernardi , José Vicente Elias (Electronic Journal "Fórum Ambiental da Alta Paulista", 2021)
This work evaluates the influence of cognitive and sociodemographic functions on the dynamics of human exposure to mercury in communities on the upper Madeira River in the state of Rondônia, Brazil. In this longitudinal epidemiological study of convenience sampling (2009 to 2019), semi-structured questionnaires on cognitive and sociodemographic aspects were applied to 1,089 participants (646 men and 443 women) divided into 6 groups with distinct geographic characteristics and lifestyles. Total mercury concentrations in hair samples were determined by direct analysis using atomic spectroscopy. In this population, cognitive (memory, attention span, concentration and difficulties in reading, writing and mathematical calculations) and sociodemographic (location, gender, age, education, alcohol consumption, smoking habits, time of residence in the region, occupation) grouping showed the differentiation between the groups with lifestyle directly related and dependent on extractivism/gold mining dispersed along the Madeira River (G1 and G2), and the groups that have urban dynamics on the margins of the federal highway BR-364 (G3, G4, G5 and G6). Sex, age and lifestyle (groups) were significant indicators of total mercury concentrations in hair. The organization of participants according to cognitive and sociodemographic profiles, regardless of geographic location, highlights the contribution of individualized social dynamics to mercury exposure in the Madeira River basin region. Despite socio-historical and socio-economic similarities, cognitive and sociodemographic functions show individualized social behaviors within communities, which may influence the process of exposure to THg.